Sosialisasi Kebersihan Pasar untuk Menciptakan Lingkungan Pasar yang Bersih, Sehat, Aman, Nyaman, dan Tertib - Martha Surya Dinata Mendrofa; Marthaeni Hulu; Siliwanus Harefa; Desi Natalis Citra Maria Ziliwu; Septry Saputra Laowo; Widya Lestari Gea; Roni Hatorangan Sitompul (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Waste that is not managed properly can have various negative impacts on the environment and public health, such as air and water pollution, aesthetic disturbances, and an increased risk of vector-borne diseases such as flies and rats. In traditional markets, this problem often arises due to the high buying and selling activities that produce various types of waste, both organic and inorganic. This study aims to identify the characteristics of waste produced in the traditional market of Gunungsitoli City, analyze the level of traders' participation in waste management, and examine the factors that affect this participation. The research methods used are a qualitative approach through direct observation in the field, in-depth interviews with traders and market visitors, and analysis of waste management policies that have been implemented by local governments and market managers. The results of the study show that even though market managers routinely socialize about cleanliness, traders' awareness to manage waste independently is still low. The main factors causing this are the limitations of waste management facilities, such as the availability of sorted waste bins, and the low understanding of traders about the adverse effects of waste on health and the environment. Therefore, continuous collaboration is needed between local governments, market managers, and the community, especially traders, to build a better cleanliness culture. Efforts that can be made include providing adequate infrastructure, training or education on waste management, and providing incentives or strict sanctions for traders so that they are more motivated to maintain cleanliness. With this integrated approach, it is hoped that waste management in the traditional market of Gunungsitoli City can run more effectively and sustainably.